2020
DOI: 10.1097/bpb.0000000000000749
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a novel predictive radiological method to assess the possibility of closed reduction in late presenting developmental dysplasia of the hip: the femoro-acetabular zones

Abstract: Late presentation of developmental dysplasia of the hip (DDH) remains a major orthopedic problem. However, existing management is not standardized and is highly surgeon dependent. The theory behind femoro-acetabular zones (FAZ) system is to find a relationship between acetabular maturity and severity of dislocation in one hand, and the outcome of closed reduction, on the other hand in late presenting cases. A retrospective study was performed on children with untreated DDH that underwent closed treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Recent studies have reported success rates ranging from 54.5% to 95.7% in patients treated with closed reduction [1,[8][9][10][11][12][13][14]. Despite these high success rates, the procedure has also been associated with complications including avascular necrosis (AVN) and failure of long-term maintenance of reduction requiring secondary reconstructive procedures [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported success rates ranging from 54.5% to 95.7% in patients treated with closed reduction [1,[8][9][10][11][12][13][14]. Despite these high success rates, the procedure has also been associated with complications including avascular necrosis (AVN) and failure of long-term maintenance of reduction requiring secondary reconstructive procedures [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%